04 FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TELUR AYAM RAS DI DESA PATTIRO DECENG KECAMATAN CAMBA KABUPATEN MAROS - Jurnal Agribis; Muh Taslim; Zulkifli Zulkifli; Abd. Asis Pata (Universitas Muslim Maros, 2021)
The purpose of this research is to know factors that affect demand for chicken eggs in the Pattiro Deceng Village, Camba District, Maros Regency. Study was conducted in january till june 2017 in the Pattiro Deceng Village, Camba District, Maros Regency. This kind of research using secondary data and the analysis used is regression. doubleThis research result that the variable, egg price income and the number of families to support no real bearing on request.